Pengaruh Lingkungan Kerja, Pengembangan Karir dan Motivasi Terhadap Kinerja Karyawan Manna Kampus Yogyakarta - Yustinus Pramono; Widarta (ASIAN PUBLISHER, 2023)
This study aims to examine the effect of the variables Career Development, Work Environment, and Motivation partially and simultaneously on the performance variables of Manna Campus Yogyakarta employees. The population in this study were employees of the Yogyakarta Campus Manna. Sampling was carried out using a purposive sampling technique and a sample of 85 respondents was obtained. Collecting data in this study using a questionnaire method. The data analysis method used is multiple linear regression analysis. The results showed that the work environment variable partially had a positive and significant effect on employee performance variables. While career development, work environment and motivation variables partially have no significant effect on employee performance variables. The results of the F test show a significance level of 0.000 which is less than the significance level of α = 0.05 so that the work environment,career development and motivation variables simultaneously have a significant effect on employee performance.